An investigation of water delivery constraints at Mabokelele village, Limpopo Province, South Africa - Manamela, Kwena France (University of Limpopo (Turfloop Campus), 2010)
The aim of the research study was to examine and analyse the main constraints faced by the Polokwane Local Municipality in delivery water services to Mabokelele Village. For the researcher to be able to achieve the aim of the study, key research questions were posed which enabled the researcher to gather / collect data that helped shed more light in the research project. Research questions such as what are the constraints faced by the Polokwane Local Municipality in water delivery services, and what strategies are been to address those constraints and how effective are those strategies, were posed to the participants of this research study. The study used the qualitative research design. Respondents were seen as experts of their own life situation. Face to face interviews were used to collect data from the participants. Data analyses was done in the form of content data analysis. The key findings of the research project:- Shortage of skills in financial management, inadequate water service infrastructure, inadequate human resource for water service delivery, lack of co-operation between the Polokwane Municipality and the Mabokelele Induna and lack of community participation and consultation by the Polokwane Local Municipality and long delays caused by the tendering process were identified as the key findings for the study. Recommendations for the study was guided by the findings of the research project. The following served as recommendations for the study : Polokwane Local Municipality should ensure that people with financial management skills and project management are employed to avoid under-spending of the budget. Community participation and consultation should be key when implementing projects to the community, Department of Water Affairs to ensure that enough water service infrastructure is provided so that the Municipality can function properly. Dwarf should speed up the transfer of officials to Polokwane Local Municipality and lastly, the red tapes in the tendering processes should be minimized to avoid long delays in the approval of water projects.
Thesis (M.Dev.) --University of Limpopo, 2010
Keywords: Water delivery problems; 553.7; Water-supply -- South Africa; Water distribution; Water-supply, Rural